Development of PjBL Model-Oriented Teaching Materials on Students Learning Outcomes - Ulfa, Luluk Nur Hamidah; Kusumaningrum, Shirly Rizki; Dewi, Radeni Sukma Indra (Jurnal Ilmiah Mandala Education (JIME), 2022)
This development research aims to: 1) Describe the results of the validity, attractiveness and practicality of the development of PjBL-oriented teaching materials to improve the science learning outcomes of Grade 6 students 2) Knowing the effectiveness and efficiency of the implementation results of the development of PjBL-oriented teaching materials to improve the learning outcomes of grade 6 students to be implemented for students. This study used an R & D (Research and Development) design using the ADDIE development model. Data collection techniques for teaching materials expert questionnaires. The results of the validation of teaching material experts showed a score of 94.2%. The small group test score obtained was 84.4 and the results of the field trial were 87. The student response questionnaire obtained results of 95. 6% can be stated that the PjBL-based science teaching materials on the adaptation of living things in class VI elementary school are very valid to be applied in science learning and for large groups the average is 95.3 with very practical criteria. The teacher response questionnaire averaged 90 with very practical criteria. The results of pretests and postes experienced an increase in the average score of the post test of 89.8 so that it can be concluded that there is an increase in scores in student learning outcomes. Based on the results of the study, it was concluded that the teaching materials for the content of PjBL-oriented science developed using the ADDIE model have good quality from the aspects of content, visual design, and grammar to be used.